Dielectrically tuned core-shell microwave-responsive sorbents for high-efficiency direct air capture - Wenjing Li; Mingxing Zhou; Xiaoyan Ji; Yunxia Wen; Han Lin; Xiaohua Lu; Xinwei Zhang; Xiwen Zhang; Tuo Ji; Shuandi Hou; Jiahua Zhu (Chemical Engineering Journal, 2026)

Integrated metabolomic, transcriptomic, and proteomic analyses reveal changes in the non-volatile metabolite profile of LED light–withered oolong tea - Qiuming Li; Yucheng Zheng; Hongzheng Lin; Yongpeng Wu; Jihang He; Xinru Yu; Mingxing Ling; Xiang Li; Jinke Lin; Zhilong Hao; Xinchao Wang; Yun Sun (Food Chemistry, 2026)

Mechanically engineered multi-oxide heterojunctions for bifunctional antibacterial and photocatalytic environmental remediation - Juan Pei; Jialan Mi; Shuhan Yao; Mingxing Guo; Ye Zhang; Xiaoling Wan; Wei Wu; Ying Hong; Pei Hu; Ping Chen; Lin Chen; Haichun Zeng; et al. (Journal of Environmental Chemical Engineering, 2026)

Spatiotemporal degradation of coastal ecosystem services in mainland China: A land-sea integrated assessment - Zhe Wang; Chengdong Wang; Mingxing Sun; Zhenhua Wang; Jun Lin (Journal of Cleaner Production, 2026)

A dual-responsive silica-based molecularly imprinted polymer for sustainable and specific adsorption of γ-aminobutyric acid from Moringa oleifera seeds - Jiabo Cheng; Jirui Sui; Xuanyi Yu; Kungang Li; Qi Liang; Chuancheng Lin; Mingxing Li; Chunying Li; Chunjian Zhao (Food Research International, 2026)

A multicomponent Fc-fused subunit vaccine induces cross-protective immunity against porcine reproductive and respiratory syndrome virus QYYZ-like and NADC30-like strains - Linxing Tian; Zhengdan Lin; Mengxi Pan; Yanwen Wen; Mingxing Lu; Shudan Liu; Chao Zhang; Zhenxiang Rong; Jiahui Ma; Ruiqu Zhou; Nan Cao; Xinghua Chen; et al. (Veterinary Microbiology, 2026)

Turning harm into benefit: Leveraging anaerobic starvation to establish novel Tetrasphaera dominated simultaneous partial nitrification, denitrification, phosphorus removal, and in-situ sludge reduction process - Zhiwei Fan; Haoyu Lin; Juannong Chen; Ziqi Zhao; Mingxing Lu; Fuping Li; Wei Zeng (Bioresource Technology, 2026)

Linking historical vegetation changes to bamboo monodominance via multi-source remote sensing - Zijian Lin; Mingxing Zhou; Yan Zhou; Liyin Wang; Zuohang Wu; Dengqiu Li (International Journal of Remote Sensing, 2026)

Promoting effect of aerobic starvation on enhancing biological phosphorus removal system - Zhiwei Fan; Zekai Ren; Yanling Guan; Ling Bai; Haoyu Lin; Ziqi Zhao; Hao Wang; Mingxing Lu; Meijie Zhou; Fuping Li; Wei Zeng (Bioresource Technology, 2026)

Microwave-driven catalytic upgrading of waste engine oil using defect-rich steel slag: Oxygen vacancy modulation and reaction mechanisms - Junhao Lin; Jiahui Hou; Jiashan Chen; Yanxi Liu; Yanan You; Mingxing Chen; Rui Ma; Hao Wang; Shichang Sun (Fuel, 2025)

Streptococcus suis employs the Ihk/Irr-PepO axis to subvert macrophage actin polymerization: A novel anti-phagocytic strategy enhancing bacterial virulence - Kaiyue Yang; Qiancheng Wang; Mingxing Liu; Dong Wei; Jinsheng Tang; Hong Zhou; Huixing Lin; Zhe Ma; Fei Pan; Hongjie Fan (Veterinary Microbiology, 2025)

Mechanochemical synthesis of ZnO@TiO2 II heterojunction material: Photocatalytic degradation and antibacterial synergistic effect - Juan Pei; Xiaoling Wan; Mingxing Guo; Jialan Mi; Wei Wu; Ying Hong; Pei Hu; Ping Chen; Lin Chen; Siwei Xiang; Qianyu Zhang; Haichun Zeng; et al. (Chemical Engineering Journal, 2025)

Filter bank temporally delayed CCA for uncalibrated SSVEP-BCI - Xiangguo Yin; Caixiu Yang; Hui Dong; Jingting Liang; Mingxing Lin (Medical & Biological Engineering & Computing, 2025)

Efficient removal of perrhenate/pertechnetate by a pyridinium-based porous polymer - Miaomiao He; Yuxuan Chen; Guangyuan Chen; Wenhao Li; Mingxing Zhang; Chao Zhang; Hao Zhang; Xingyi Long; Kui Tang; Tao Duan; Lin Zhu (Environmental Pollution, 2024)

Time–frequency feature extraction based on multivariable synchronization index for training-free SSVEP-based BCI - Xiangguo Yin; Mingxing Lin; Jingting Liang; Fanshuo Zeng (Cognitive Neurodynamics, 2024)

Resistance of CANON systems with different granules/flocs sludge ratios to alternating low-temperature operation - Siyun Liu; Bolin Li; Xiang Li; Xiangyu Lin; Wanqing Zhao; Hai Su; Mingxing Yu (Journal of Water Process Engineering, 2024)

Characterization of methyltetrahydrophthalic anhydride esterified corn starch and their ability in stabilizing Pickering emulsion - Yang Zhong; Yi Lin; Mingxing Yang; Xiaodan Zeng; Dayu Liu; Wenlong Liu; Weijun Chen (Journal of Food Engineering, 2024)

Multi-information improves the performance of CCA-based SSVEP classification - Xiangguo Yin; Mingxing Lin (Cognitive Neurodynamics, 2024)

Electrochemical CO2 reduction to C2+ products with Cu-oleylamine based nanoparticles synthesized by simple thermal treatment - Xinyu Liu; Jingzheng Li; Yuan Xue; Mingxing Gong; Carlos R. Cabrera; Lin Yao; Zhongfa Hu (Fuel, 2023)

An Improved YOLOv5s-Based Scheme for Target Detection in a Complex Underwater Environment - Chenglong Hou; Zhiguang Guan; Ziyi Guo; Siqi Zhou; Mingxing Lin (Journal of Marine Science and Engineering, 2023)
At present, sea cucumbers, sea urchins, and other seafood products have become increasingly significant in the seafood aquaculture industry. In traditional fishing operations, divers go underwater for fishing, and the complex underwater environment can cause harm to the divers’ bodies. Therefore, the use of underwater robots for seafood fishing has become a current trend. During the fishing process, underwater fishing robots rely on vision to accurately detect sea cucumbers and sea urchins. In this paper, an algorithm for the target detection of sea cucumbers and sea urchins in complex underwater environments is proposed based on the improved YOLOv5s. The following improvements are mainly carried out in YOLOv5s: (1) To enhance the feature extraction ability of the model, the gnConv-based self-attentive sublayer HorBlock module is proposed to be added to the backbone network. (2) To obtain the optimal hyperparameters of the model for underwater datasets, hyperparameter evolution based on the genetic algorithm is proposed. (3) The underwater dataset is extended using offline data augmentation. The dataset used in the experiment is created in a real underwater environment. The total number of created datasets is 1536, and the training, validation, and test sets are randomly divided according to the ratio of 7:2:1. The divided dataset is input to the improved YOLOv5s network for training. The experiment shows that the mean average precision (mAP) of the algorithm is 94%, and the mAP of the improved YOLOv5s model rises by 4.5% compared to the original YOLOv5s. The detection speed increases by 4.09 ms, which is in the acceptable range compared to the accuracy improvement. Therefore, the improved YOLOv5s has better detection accuracy and speed in complex underwater environments, and can provide theoretical support for the underwater operations of underwater fishing robots.

Preparation of photocatalysts decorated by carbon quantum dots (CQDs) and their applications: A review - Feixia Zhao; Xueying Li; Mingxing Zuo; Yunshan Liang; Pufeng Qin; Hui Wang; Zhibin Wu; Lin Luo; Chao Liu; Lijian Leng (Journal of Environmental Chemical Engineering, 2023)

Coinfection with porcine circovirus type 2 and Glaesserella parasuis serotype 4 enhances pathogenicity in piglets - Mengru Guo; Kaiyue Yang; Shaojie Lin; Jinsheng Tang; Mingxing Liu; Hong Zhou; Huixing Lin; Hongjie Fan (Veterinary Microbiology, 2023)

Coupled impacts of climate and land use changes on regional ecosystem services - Lin Sun; Huajun Yu; Mingxing Sun; Yutao Wang (Journal of Environmental Management, 2023)

Distribution, sources, and ecological risk of organophosphate esters in the urbanized Jiaozhou Bay, East China - Jianing Lin; Lutao Zhang; Mingxing Zhang; Heng Zhang; Changsheng Guo; Song Feng; Jian Xu (Environmental Science and Pollution Research, 2022)

Expression profiling of WRKY transcription factors in Spinach - Yaying Ma; Shuai Chen; Hongying Yu; Ruoyu Li; Zhicong Lin; Mingxing Cai; Min Tang; Xingtan Zhang; Ray Ming (Euphytica, 2021)

Effects of Grazing, Wind Erosion, and Dust Deposition on Plant Community Composition and Structure in a Temperate Steppe - Mengmei Zheng; Jian Song; Jingyi Ru; Zhenxing Zhou; Mingxing Zhong; Lin Jiang; Dafeng Hui; Shiqiang Wan (Ecosystems, 2021)

Filter bank temporally local canonical correlation analysis for short time window SSVEPs classification - Xinghan Shao; Mingxing Lin (Cognitive Neurodynamics, 2020)

Temporal variations in riverine hydrochemistry and estimation of the carbon sink produced by coupled carbonate weathering with aquatic photosynthesis on land: an example from the Xijiang River, a large subtropical karst-dominated river in China - Rui Yang; Hailong Sun; Bo Chen; Mingxing Yang; Qingrui Zeng; Cheng Zeng; Jie Huang; Huixian Luo; Danhui Lin (Environmental Science and Pollution Research, 2020)

Identification and Expression Analysis of TCP Genes in Saccharum spontaneum L - Jishan Lin; Mengting Zhu; Mingxing Cai; Wenping Zhang; Mahpara Fatima; Haifeng Jia; Feifei Li; Ray Ming (Tropical Plant Biology, 2019)

Urban metabolic efficiencies and elasticities of Chinese cities - Tao Song; Jianming Cai; Zhenshan Yang; Mingxing Chen; Jing Lin (Chinese Geographical Science, 2016)

The genetic association of adakites and Cu–Au ore deposits': a reply - Weidong Sun; Mingxing Ling; Xing Ding; Sun-Lin Chung; Xiao-Yong Yang; Weiming Fan (International Geology Review, 2012)